Fracture modes of AISI type 302 stainless steel under metastable plastic deformation - SANTOS, Jheison Lopes dos (Associação Brasileira de Metalurgia e Materiais, 2019)
Martensitic transformation can be induced by plastic deformation in metastable iron-based alloys, such as stainless steels containing limited amounts of C, Ni and Cr. This transformation takes place at the temperature range from Ms and Md, usually at relatively lower temperature values. The transformed martensite has been associated with maximum ultimate strength and relatively high ductility. In the present work, the tensile fracture characteristics of a metastable AISI type 302 stainless steel was properties were compared to those of a stable AISI type 310 austenitic stainless steel. It was found that in 302 steel, its high degree of metastability and dilute dispersion of inclusions result in higher strength and complex modes of fracture, one of which consisting of martensite surrounding globular inclusions.